Penerapan Etika Profesi Akuntansi dalam Pengembangan Usaha Tanaman Kangkung untuk Meningkatkan Kesejahteraan Masyarakat - R. Mohd Zamzami; Ahmad Syauqi; Rananda Septanta; Chaeru Syahru Ramdani (Jurnal PKM Manajemen Bisnis, 2026)
This community service activity (PKM) is motivated by the need to improve community welfare through sustainable small-scale agribusiness while integrating professional accounting ethics. Many communities, including orphanages, have limited knowledge of ethical financial management and business development, which can hinder the growth and sustainability of their economic activities. Therefore, this program aims to enhance participants’ understanding of accounting professional ethics and its application in developing a water spinach (kangkung) cultivation business. The PKM was conducted at a foundation for orphans in Pamulang, South Tangerang, on April 19, 2026. The activity involved five lecturers from Universitas Pamulang and was attended by 24 participants, consisting of children and teachers from the foundation. The implementation methods included material presentation, hands-on practice, discussion, and question-and-answer sessions. The stages of the activity consisted of preparation, implementation, and reporting. The results of the activity indicate an increased understanding among participants regarding ethical financial practices and improved skills in cultivating and managing a small-scale kangkung business. Participants showed enthusiasm and active engagement throughout the program, suggesting the effectiveness of the applied methods.